2022
DOI: 10.2147/idr.s353130
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Carbapenem-Resistant ST244, ST292, and ST2446 Pseudomonas aeruginosa Clones in Burn Patients in Yunnan Province

Abstract: Introduction The prevalence of carbapenem-resistant Pseudomonas aeruginosa is increasing persistently, particularly in burn ward isolates. Here, we investigate the prevalence of carbapenem-resistant Pseudomonas aeruginosa in a burn ward of a provincial-level hospital at Kunming, Yunnan province, China. Methods A total of 118 P. aeruginosa strains were isolated from 57 hospitalized patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…3). cgMLST analyses revealed that the closest relatives of P. aeruginosa DMC30b genome were one carbapenem-resistant ST244 P. aeruginosa clone in burn patients in Yunnan province, China [17], and another ST244 strain, P. aeruginosa MRSN 17623, clinical isolate carrying the blaVIM-6 gene recovered from human in the USA (https://www.pseudomonas.com/strain/show/2623) which differed by 285 cgMLST loci (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3). cgMLST analyses revealed that the closest relatives of P. aeruginosa DMC30b genome were one carbapenem-resistant ST244 P. aeruginosa clone in burn patients in Yunnan province, China [17], and another ST244 strain, P. aeruginosa MRSN 17623, clinical isolate carrying the blaVIM-6 gene recovered from human in the USA (https://www.pseudomonas.com/strain/show/2623) which differed by 285 cgMLST loci (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of these carbapenemases in high-risk clones and sequence types (STs) on complete genome or plasmid or the chromosome of P. aeruginosa, may be the cause of its successful dissemination in Bangladesh and beyond. Recent molecular and genomic studies reported that most of the infectious and virulent clones of P. aeruginosa belonged to ST235, ST244, ST308, ST1006, and ST1060 [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Muddassir et al, 2021;Fang et al, 2022). Additionally, controlling the strains resisting drugs and preventing from dissipation of such infections in health care centers is considered necessary(Eslami et al, 2018;Ghasemian et al, 2018).…”
mentioning
confidence: 99%
“…For the first time, ST244 is reported emerging in burn patients which exhibited a higher level of resistance to several antibiotics. The obtained results highlight the need to surveillance MDR-resistant isolates in burn patients [17, 47]. Epidemiological source tracking revealed that the P. aeruginosa DMC30b strain has close evolutionary relationship with many strains of P. aeruginosa originating from a wide arsenal of clinical samples including enteritis, gastroenteritis (diarrheal diseases), urinary tract infections, and both community- and hospital-acquired bacteraemia in humans and animals (e.g., dog).…”
Section: Resultsmentioning
confidence: 94%